Reflective acoustic jet from a mesoscale concave mirror. (1st February 2023) - Zhou, Song; Wang, Yalin; Chen, Zhong; Gao, Rong; Yang, Quanquan
Abstract: An acoustic jet (AJ) is similar to a photonic nanojet (PNJ) in achieving high-intensity and sub-wavelength scale focus. Herein, we numerically investigate a reflective acoustic jet (r-AJ) generated by a mesoscale concave mirror using the finite element method. A sub- λ /2 rotational symmetric r-AJ can be produced by an air-filled polylactic acid (PLA) spherical concave mirror immersed in water under a plane acoustic wave. And the properties of r-AJ affected by the concave angle of the mirror are also presented. By combining a PLA spherical structure with the concave mirror, a sub- λ /3 near-field r-AJ can be achieved. We also present the streamlines of the time-averaged acoustic intensity vectors near the r-AJ and the influence of the structural loss of the designed PLA mirror on the r-AJs. The influences of the incident frequency change and PLA properties change on the r-AJs generation and the slight angle between the incoming field and the mirror are presented. Finally, we numerically discuss the potential application of our designed mirror in direct sound printing.